Vascular Access Related Infections in Hemodialysis Children and the Impact of Implementation of CDC Guidelines and Tools on the Control of these Infections: A Single Centre Experience from Egypt - El Moselhy, Sawsan S.; El-Sharawi, Mohamed Nasr; Abd Elhady, Marwa Waheed; Ibrahim Qasim, Mohamed Awad; Said, Ragia Marei (International Journal of Child Health and Nutrition, 2024)
Background: Vascular access-related infection (VARI) is a serious issue in pediatric end-stage kidney disease (ESKD) patients on regular hemodialysis. Objective: To estimate the frequency of vascular access-related infections in hemodialysis (HD) children and to assess the effect of the implementation of CDC guidelines and tools on the prevention of VARI. Subjects and Methods: This study was conducted on 110 patients with ESKD on regular hemodialysis at the Pediatric Dialysis Unit, Ain Shams University, from August 2019 to September 2021, retrospectively for one year and prospectively for another year after implementing the CDC infection control procedures. Besides full history taking, vascular access history, and thorough clinical examination, lab investigations for VARI diagnosis and echocardiography were performed. CDC infection control procedures were implemented for one year, and VARI was re-evaluated. Results: The total number of patients enrolled in the study was 110, they were 58 males (52.7%) and 52 females (47.3%). The incidence of infection per 1000 vascular access days in both years was highest in patients with NTVCs (10.447 /1000 NTVC days, 6.861 /1000 NTVCs days), followed by patients with TVCs (1.051/1000 TVC days, 0.604 /1000 TVC days) then patients with AVF, (0.141/1000 AVF days, 0.046 /1000 AVF days). The mortality from vascular access-related infections in the first year was higher than in the second year, with 5 patients (10.2%) and 1 patient (3.8%), respectively. The average duration of hospital stays (PPY) due to VARI (total admission days 8.09 and ward admission days 6.41) in the first year were significantly higher than in the second year, 4.04, 3.20 days/PPY, respectively. Conclusion: The incidence of vascular access infection (VAI) is higher with non-tunneled catheters and lowest with Arteriovenous fistulae (AVF). To reduce the risk of VARI and hospitalization, proper infection control procedures must be implemented.